199k views
1 vote
If you don't see what it says it's says : equivalent the expression for v= - 6/7

If you don't see what it says it's says : equivalent the expression for v= - 6/7-example-1
User Yikouniao
by
4.9k points

1 Answer

5 votes

Answer:

Explanation:

To evaluate the expression for v = -6 / 7, we put this value in instead of v to get


-12(1)/(2)-3(-(6)/(7))

Which upon simplification becomes


-12(1)/(2)+(6\cdot3)/(7)
-(25)/(2)+(6\cdot3)/(7)
=-(25)/(2)+(18)/(7)
=-(139)/(14)

which is our answer!

User Steadweb
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.